Problemy ochrony prawnej zabytkowych militariów. Uwagi de lege lata i de lege ferenda - Lewandowski, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
This article is merely a small contribution to a discussion that has been going on for some time now regarding the protection of a very particular subtype of historic objects, namely militaria. It describes the main issues behind their protection, indicating, among other factors, many years of negligence; ineffective law; lack of a vision for modern military museums; indolence of heritage protection institutions, law enforcement and judicial authorities; and missing regulations concerning collector activities. The author examines the reasons for the current state of affairs and suggests possible solutions.
Keywords: legal protection of historic military objects